Media Pembelajaran Interaktif Berbasis Video Dalam Penggunaan Scan Tool Tipe Launch Thinkdiag Easydiag 4.0 - Amril, Febri Caesar; Tri Tunggal Wicaksono; Heru Budi Setiaji; Hamid Nasrullah (JASATEC : Journal Students Of Automotive, Electronic and Computer, 2021)
This study aims to make it easier for students to understand the use of scan tools, especially the Thinkdiag Easydiag 4.0 launch type scan tool. In order to improve the quality of learning in the Automotive Mechanical Engineering department, more interactive learning media are need-ed. In this final project, the method used is a quantitative method. As for the source of the data obtained based on the dissemination of information in the form of a questionnaire addressed to students who have used interactive media during learning. Based on the testing of this final pro-ject, it resulted in a score of 56.7% of the total student respondents. So that students can easily understand the material for using the Thinkdiag Easydiag 4.0 launch type scan tool thanks to interactive learning media.